Learning Effectiveness Of STEAM Video Making Fruit Salad In Improving Early Childhood Cognitive Skills - Wiyarno, Indro; Erna Budiarti (Kirana Publisher (KNPub), 2024)
This study aims to determine the effectiveness of using STEAM learning videos about fruit salad making in improving cognitive skills of children aged 5-6 years at Rising Stars Kindergarten Jakarta. The research type used is experimental research with a one-group pretest-posttest design. The research population comprises all 20 students aged 5-6 years at Rising Stars Kindergarten Jakarta. The sampling technique uses total sampling, so the entire population is used as the research sample. The data collection technique uses structured observation with an instrument in the form of an observation sheet consisting of 10 items to measure children's cognitive skills, including the ability to observe, compare, classify, and solve simple problems. The instrument's validity was tested using construct and content validity, while reliability was tested using Cronbach's Alpha. The data analysis technique uses descriptive and inferential statistics. The prerequisite analysis test includes a normality test with Kolmogorov-Smirnov and a homogeneity test. Hypothesis testing uses a paired sample t-test with a significance level of 0.05. The results show a significant increase in the average score of children's cognitive skills from 42.875 in the pre-test to 83.750 in the post-test. Hypothesis testing yields a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between pre-test and post-test results.